Better Together? Intimate Partner Effects on Offending Women - Lee, Jacqueline G. (Journal of developmental and life-course criminology, 2020)
The role of marriage has been extensively studied for its positive impacts on male desistance. However, the role of romantic partners for women is less understood. Do partners exert a prosocial “protective” effect or are they criminogenic? The present study empirically drills down on this question. Specifically, we assess the character and quality of romantic relationships on substance use and illegitimate income using a sample of incarcerated women. Drawing from social control, social learning, and strain theory, we hypothesize that the effects of both being in and breaking up from a relationship on illicit behavior are conditional on the quality of the relationship and behavior/characteristics of the partner. Using data from the Women’s Experience of Violence (WEV) project, consisting of a custodial sample of criminal justice-involved women (N = 770), we examine how relationship status and quality, as well as partner offending, influence drug use and illicit earnings. A series of multi-level random effects models are estimated to explore how within-person changes in relationship/breakup status are related to changes in the two dependent variables. Contrary to expectations, we find that romantic dissolution (of either a high- or low-quality relationship) does not negatively impact this sample of women and that being in a high-quality relationship is not a protective factor, as has been found often in male samples. Findings suggest partner behavior may be more important than the quality of the relationship with the partner. Our results link drug use and participation in the illicit economy to factors mostly outside of a woman’s relationship status and quality, thereby challenging some commonly understood mechanisms of desistance.